2007
DOI: 10.1007/s00405-007-0473-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for vestibular impairment in sensorineural hearing loss

Abstract: The clinical course and prognosis in sensorineural hearing loss (SNHL) may be even worse if vestibular system is also involved, especially due to near location of anatomical structures in the inner ear. The aim of the study was to determine prognostic value of some clinical, audiological and demographic factors associated with SNHL in predicting a possibility of vestibular impairment. The study was conducted on 124 consecutive patients (183 ears) diagnosed for sensorineural hearing loss during 1 year in our de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
2
12
1
1
Order By: Relevance
“…We found that vestibular dysfunction occurs more often in cases with severe to complete hearing loss. This observation is in agreement with previous reports for different etiologies, that peripheral vestibular impairment was found mainly among those with residual deafness 19 or co-incidence of balance system dysfunction was more frequent in profound hearing loss. 20 Similar to hearing loss, vestibular imbalance persists in a large majority of cases after 9 months with a similar rate among retrospectively enrolled cases, suggesting a permanent loss of function.…”
Section: Discussionsupporting
confidence: 93%
“…We found that vestibular dysfunction occurs more often in cases with severe to complete hearing loss. This observation is in agreement with previous reports for different etiologies, that peripheral vestibular impairment was found mainly among those with residual deafness 19 or co-incidence of balance system dysfunction was more frequent in profound hearing loss. 20 Similar to hearing loss, vestibular imbalance persists in a large majority of cases after 9 months with a similar rate among retrospectively enrolled cases, suggesting a permanent loss of function.…”
Section: Discussionsupporting
confidence: 93%
“…The results were different to Pajor & Jozefowicz-Korczynska [1] , who noted abnormal ENG in 88% of patients (22 ears); in nearly all of them (20 ears), vestibular impairment was of peripheral type. They also reported that in children with SNHL, concomitant damage to vestibular structures is commonly reported.…”
Section: Discussioncontrasting
confidence: 86%
“…Disturbances in cochlear function, which can result in sensorineural hearing loss (SNHL), could accompany vestibular impairment because the cochlea and the vestibule share the continuous membranous labyrinth of the inner ear, therefore, injury or trauma prenatally, perinatally, or postnatally may cause damage to one or both systems [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…The vestibular end-organ and cochlea are closely related both anatomically and functionally. Therefore, injury or trauma prenatally, perinatally, or postnatally may cause damage to one or both systems [28-30]. Moreover, damage to portions of the vestibule-cochlear nerve is a presumed cause of sensorineural hearing loss, may include damage to both cochlear apparatus as well as the vestibular afferents [31].…”
Section: Patho-physiology Of Postural Control and Motor Development Imentioning
confidence: 99%